Acoustic‐Pressure‐Assisted Engineering of Aluminum Foams. Issue 7 (14th April 2021) - Mettan, Xavier; Martino, Edoardo; Rossi, Lidia; Jaćimović, Jaćim; Krsnik, Juraj; Barišić, Osor S.; Babcsán, Norbert; Beke, Sándor; Mokso, Rajmund; Kaptay, George; Forró, László
Abstract : Shaping metals as a foam modulates their physical properties, enabling attractive applications where lightweight, low thermal conductivity, or acoustic isolation are desirable. Adjusting the size of the bubbles in the foams is particularly relevant for targeted applications. Herein, a method with a detailed theoretical understanding of how to tune the size of the bubbles in aluminum melts in situ via acoustic pressure is provided. The description is in full agreement with the high‐rate 3D X‐ray radioscopy of the bubble formation. The study with the intriguing results on the effect of foaming on electrical resistivity, Seebeck coefficient, and thermal conductivity from cryogenic to room temperature is complemented. Compared with bulk materials, the investigated foam shows an enhancement in the thermoelectric figure of merit. These results herald promising application of foaming in thermoelectric materials and devices for conversion of thermal energy. Abstract : Metal foams enable attractive applications where lightweight, low thermal conductivity or acoustic isolation are desirable. Target performances can be obtained by tuning the dimension of the cells inside of the foam, by means of acoustic pressure directly during the foaming process. Experimental characterisation of thermal and electrical properties, in particular the Seebeck coefficient, for an aluminium foam demonstrate a global strategy to enhance energy‐conversion efficiency of thermoelectric materials.